Analysis of Clinical Nurses’ Happiness Levels Using the Oxford Happiness Questionnaire in a Hospital - Risnawati Risnawati; Julida Julida (An Idea Nursing Journal, 2026)
Background: Nurses’ happiness is a critical determinant of job satisfaction and quality of care. Adverse working conditions, shift schedules, and heavy workloads can diminish nurses’ happiness. Objective: Identifying the level of happiness and its primary contributing factors among clinical nurses is therefore essential. Methods: This study utilized a descriptive quantitative approach with the Oxford Happiness Questionnaire. Seventy-three clinical nurses from five inpatient wards at Hasanuddin University Hospital in Makassar were selected through purposive sampling. Results: Most respondents reported a very high level of happiness (87.7%), while 12.3% reported a high level. The most significant contributing aspect was the perception that "life is rewarding" (97.3%), followed by "happy memories" (94.5%) and being "pleased with life" (93.2%). Factors associated with higher happiness included the absence of additional employment, effective time management, higher education level, marital status, and higher income. Conclusion: Clinical nurses in inpatient wards at Hasanuddin University Hospital predominantly experience very high levels of happiness, with the perception of a meaningful life emerging as the most influential factor. Both individual and organizational factors contribute to these outcomes. Hospitals should sustain and strengthen supportive work environments by managing workloads, facilitating career development, and providing psychological support programs. Future research should incorporate additional variables, such as burnout and social support, and employ more comprehensive research designs.